2010
DOI: 10.1016/j.neuron.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Depresses Synaptic Transmission in Sympathetic Ganglia by Inactivating nAChRs through a Conserved Intracellular Cysteine Residue

Abstract: Most people with diabetes develop severe complications of the autonomic nervous system; yet, the underlying causes of many diabetic-induced dysautonomias are poorly understood. Here we explore the idea that these dysautonomias results, in part, from a defect in synaptic transmission. To test this idea, we investigated cultured sympathetic neurons and show that hyperglycemia inactivates nAChRs through a mechanism involving an elevation in reactive oxygen species and an interaction with highly conserved cysteine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 33 publications
5
78
0
2
Order By: Relevance
“…For adrenal medullae, we used Ca 2ϩ -and Mg 2ϩ -free HBSS. The resulting cell suspension was washed twice in serum-containing medium and plated on laminin-coated coverslips attached to modified 35 mm culture dishes (Campanucci et al, 2008). Sympathetic neurons were grown in media consisting of L-15 supplemented with 5 mM glucose, vitamins, cofactors, penicillin-streptomycin, 5% rat serum, and 25 ng/ml nerve growth factor (NGF).…”
Section: Primary Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…For adrenal medullae, we used Ca 2ϩ -and Mg 2ϩ -free HBSS. The resulting cell suspension was washed twice in serum-containing medium and plated on laminin-coated coverslips attached to modified 35 mm culture dishes (Campanucci et al, 2008). Sympathetic neurons were grown in media consisting of L-15 supplemented with 5 mM glucose, vitamins, cofactors, penicillin-streptomycin, 5% rat serum, and 25 ng/ml nerve growth factor (NGF).…”
Section: Primary Culturesmentioning
confidence: 99%
“…ACh-evoked currents were measured with whole-cell patch clamp as described previously (Campanucci et al, 2008). Membrane currents were recorded with a VE-2 amplifier (Alembic Instruments) at room temperature and were filtered and analyzed offline with Igor software.…”
Section: Whole-cell Recordingsmentioning
confidence: 99%
“…It is interesting to note that the cysteine that is palmitoylated in our study has been suggested to undergo reactive oxygen species-regulated use-dependent inactivation in the ␣3␤4 nAChR (14). The authors propose that use-dependent inactivation of the ␣3␤4 nAChR occurs after the receptors have been repeatedly exposed to agonist over time due to mild elevations in reactive oxygen species (14,21,22).…”
Section: Discussionmentioning
confidence: 68%
“…The authors propose that use-dependent inactivation of the ␣3␤4 nAChR occurs after the receptors have been repeatedly exposed to agonist over time due to mild elevations in reactive oxygen species (14,21,22). Receptor use can also enhance the depalmitoylation of proteins (23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation